Interventions that Enhance Breastfeeding Initiation, Duration, and Exclusivity: A Systematic Review. Issue 5 (September 2016) - Wood, Natsuko K.; Woods, Nancy F.; Blackburn, Susan T.; Sanders, Elizabeth A.
Abstract: Objective: The purpose of this review was to evaluate breastfeeding interventions trialed to date and recommend directions for future needs in breastfeeding research. Methods: A literature review was conducted using PubMed, CINAHL Plus, and PsycINFO databases to identify studies that evaluated efficacy or effectiveness of breastfeeding interventions on breastfeeding initiation, duration, or exclusivity as a primary, secondary, or tertiary outcome. Combinations of search terms included breastfeeding, feeding behavior, prenatal/patient education, health promotion, social support, perinatal/prenatal/intrapartum/postnatal care, and postpartum period. Results: Six studies were included in this review, using PRISMA guidelines. Acquisition of knowledge and skills, emotional support by healthcare providers, and self-efficacy over maternal confidence in her ability to breastfeed were factors the intervention studies relied on to affect breastfeeding practices. Although these factors were addressed in the studies, breastfeeding mothers had difficulty transferring what they gained from interventions into their real-life breastfeeding practices as evidenced by the highest drop-off rate of exclusive breastfeeding in the early postpartum. Conclusions: There were conceptual limitations to the reviewed studies: (1) lack of understanding of maternal perception of infant behavior and (2) perceived insufficient milk as a remaining primary reason for breastfeeding discontinuation. There were methodological limitations: (1) lack of theory-based interventions and (2) lack of intervention fidelity. Future studies involving breastfeeding should focus on the causes of the problems driven by theory-based interventions integrated with intervention fidelity. Abstract : Results of this systematic review highlight the significant gaps in knowledge about effective interventions to promote successful breastfeeding.